(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this work series of new aromatic Polyesters were synthesized by polycondensation of various aromatic monomers di hydroxyl .this monomers containing on pyridine heterocyclic ring ,aliphatic methylene linkage and 4,4-Azo di benzoic acid (BCHPBM, BHPFM,FBHP,CPBHP) with Acids(4,4Azo di benzoic acid, phthalic acid and Maleic acid) using dibutyltine dilaurate as Catalyst .all polyesters(P.E1-P.E4)containing pyridine heterocyclic ring, aliphatic methylene linkage, and Azo group. The yield of Polyesters varies from 75-88%. All of these new aromatic polyester show very good solubility in common organic solvents, such as (pyridine, CHCl3, CH2Cl2 , NaOH, H2SO4, HNO3, acetone, benzene, DMF, DMSO, THF) without need for heating. Thermal stability of polyesters was studied using thermo gravimetric analysis (TGA). Monomers and polyesters characterized by spectrosticcopyFT-IRand1HNMR.